2021
DOI: 10.1097/gox.0000000000003676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Geographic Distribution of the Integrated Plastic Surgery Match

Abstract: Background: COVID-19 had significant impact on the 2021 integrated plastic surgery match, most notably through cancellation of away rotations and virtual interviews. While previous studies have analyzed geographic outcomes of the match in prior years, the effects of COVID-19 have not been determined. This study aims to contribute 2021 match data to determine the effects of COVID-19 on the geographic distribution of the integrated plastic surgery match. Methods: Official… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Evaluating the possibility of unexpected impacts of the virtual interview process for the 2020-2021 application cycle was the primary focus of this study. In the integrated plastic surgery Match, an increase in the percentage of residents matching in the same region [14,15] and an increase in programs matching internal candidates [15] was observed. This is in contrast to neurology, where no significant changes in the national or regional matching patterns were identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the possibility of unexpected impacts of the virtual interview process for the 2020-2021 application cycle was the primary focus of this study. In the integrated plastic surgery Match, an increase in the percentage of residents matching in the same region [14,15] and an increase in programs matching internal candidates [15] was observed. This is in contrast to neurology, where no significant changes in the national or regional matching patterns were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The abrupt transition to virtual interviews in the setting of a global pandemic raised the concern that geography could become an even greater factor. This concern was supported by data from plastic surgery showing an increase in the number of students matching to their home program or programs within the same region (particularly in the Midwest) [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…In addition to preferences for in-person interviews, concerns exist about the implications of virtual interviews on match outcomes. Virtual interviews resulted in a higher rate of matching at a student’s home institution [ 16 , 17 ]. There is evidence that some program directors are concerned that applicants from less prestigious schools are at a disadvantage in the era of virtual interviews and limited away rotations [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies evaluating 2021 match data showed a significant increase in applicants matching at their home institutions compared with previous years. [8][9][10][11][12][13][14][15] The link between these changes and the COVID-19 pandemic has been described in detail. Among students interested in plastic surgery, COVID-19 not only affected the residency application process but also negatively impacted these students' confidence in their medical education.…”
Section: Introductionmentioning
confidence: 99%